Analysis of the nutritional composition and organization of school meals in the province of Kadiogo in Burkina Faso: challenges and prospects - Compaoré, Ella W. R.; Ouédraogo, Ousmane; Souho, Tiatou; Bengaly, Marcel D.; Simporé, Mamouna P.; Dicko, Mamoudou H. (Frontiers in Nutrition, 2024)
Background: In the face of food shortages and precariousness, school meals are an effective means of encouraging pupils to attend and stay in school, and of combating nutritional deficiencies. Unfortunately, there are bottlenecks to be identified and resolved.Objective: Analysing the composition of meals served to school-age children in primary schools in the province of Kadiogo, while assessing the opinion of school staff on these meals (Burkina Faso).Methods: A descriptive cross-sectional survey about school meals was carried out during the period from April to May 2019 among school stakeholders in primary schools in five (05) municipalities of the province of Kadiogo.Results: Insufficient quantity and quality of rations served were recorded in primary schools. The endogenous initiative canteens represented 46.4% of the registered canteens. The promotion of Health-Hygiene-Nutrition (H-H-N) activities in schools encountered difficulties in covering the sanitary needs of school-aged children because unavailability of socio-sanitary infrastructures.School meals consisted of starchy foods and legumes in rural schools and more diversified meals consisting of fruits and vegetables as well as meat and fish in urban schools. In rural municipalities, school meals were insufficient in quantity and quality, while in the urban municipality, macronutrient intakes were in excess with micronutrient intakes largely deficient.Despite the shortcomings, school officials specified that school meals cover lunch rations, increase school enrolment, and improve school-aged children' learning capacity.